Knowledge of cervical cancer, human papillomavirus and prevention among first-year female students in residences at the University of the Free State - Nathaniel Mofolo; Maarasi Sello; Moleboheng Leselo; Naledi Chabanku; Samke Ndlovu; Quandry Naidoo; Gina Joubert (AOSIS, 2018)
Background: Cervical cancer is the second most common cancer among women in South Africa. One of the major risk factors for the development of cervical cancer is the human papillomavirus (HPV). Aim: To determine the knowledge of first-year female students living in residences on the main campus of the University of the Free State (UFS) regarding cervical cancer and HPV. Setting: Female residences on the main campus of UFS. Methods: A descriptive cross-sectional study was conducted on participants between the ages of 18 and 25 years using a non-random convenience sampling method. Seven residences were included. Anonymous self-administered questionnaires were distributed during the eveningmeetings to all first-year female students at the selected residences after an information session.Students had to complete the questionnaires immediately after the meeting. Results: Most of the 373 respondents (85.8%) knew that cervical cancer arises from the cervix, but only 15.4% knew that it was caused by a virus. Of the 62.5% participants who knew that HPV was a cancer-causing virus, most correctly knew that HPV was contracted by unprotected sexual intercourse (81.1%) and that there is a vaccine to protect against HPV (73.1%). However, 62.0% knew that the vaccine was available in South Africa and only 31.0% knew the vaccine was free of charge. Conclusion: The study revealed that students had limited knowledge of cervical cancer, HPV and vaccine availability.